Bilateral benign renal oncocytomas and the role of renal biopsy: single institution review. Issue 1 (December 2017) - Leone, Andrew; Kidd, Laura C.; Diorio, Gregory; Zargar-Shoshtari, Kamran; Sharma, Pranav; Sexton, Wade; Spiess, Philippe
Abstract Background The goal was to assess the natural history and management of patients with pathologically proven bilateral (synchronous) RO after undergoing initial partial nephrectomy (PN). Methods All patients underwent either robotic/laparoscopic or open PN by two experienced genitourinary oncologists from 2005–2013. Final pathology was determined by surgical excision, CT-guided percutaneous core biopsy (CT-biopsy) or fine needle aspiration (FNA). Patient demographics, tumor characteristics (pathologic data, location, size) type of surgery, pre/post estimated glomerular filtration rate (eGFR) and surgical complications were recorded. Results Twelve patients were identified with bilateral RO. Median age at the time of surgery was 68 years (46–77) (Table 1). The median size of the largest tumor(s) resected was 2.75 cm (1.5–5.5 cm) and second largest tumor(s) was 1.75 cm (1.0–4.0 cm). Four patients underwent bilateral staged PN and one patient underwent simultaneous bilateral PN (horseshoe kidney). Two patients underwent RFA at the time of biopsy of the contralateral mass after PN. Five patients underwent CT-bx/FNA (5/5) of the contralateral mass followed by active surveillance. Mean follow up was 34 months. There was no significant change in median creatinine pre- and post-operatively. One patient was lost to follow up and one patient died of unknown causes 5 years post-operatively. eGFR decreased an average of 16.96% post-operatively, including a single patient whose eGFR increased by 7.8% after surgery and a single patient whose eGFR did not change (Table 2). Conclusions Patients with bilateral renal masses and pathologically proven RO can be safely managed with active surveillance after biopsy confirmation of the contralateral mass.